Maximality and first-order criteria of r-monotone operators. (2nd August 2020) - Fajri, Youness Alhabib; Hassouni, Abdelhak
ABSTRACT: In this article, the new notions of maximal r -monotone operator and r -polar are introduced and studied. Then, first-order characterizations for smooth and locally Lipschitz r -monotone maps are established. As a corollary, new second-order characterizations of r -convex functions are derived.